2014
DOI: 10.1007/978-3-319-12157-4_35
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Tool on Time Perception of Children with ADHD

Abstract: Abstract. ADHD is among the most common childhood developmental disorder which may affect the school achievements. Children with ADHD may show symptoms of time perception problems. Although ADHD is a clinical diagnosis with several approaches, no diagnostic tool has been designed to detect the symptoms of time perception problems in ADHD children. A computer game can be a powerful tool to be used as part of the psychological assessment and yield better accuracy in ADHD diagnosis. In this paper, we present our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A recent study based on duration discrimination and controlled for a possible impulsivity bias has indicated the presence of a faster internal clock in children with ADHD [ 51 ]. Hence, a “pure” time perception deficit in ADHD has been assumed [ 44 ] and its use for diagnostics has been discussed [ 21 ]. In addition to the duration discrimination method, studies on temporal processing in ADHD have commonly employed reproduction and verbal time estimation tasks [ 7 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study based on duration discrimination and controlled for a possible impulsivity bias has indicated the presence of a faster internal clock in children with ADHD [ 51 ]. Hence, a “pure” time perception deficit in ADHD has been assumed [ 44 ] and its use for diagnostics has been discussed [ 21 ]. In addition to the duration discrimination method, studies on temporal processing in ADHD have commonly employed reproduction and verbal time estimation tasks [ 7 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the challenge in clinical diagnostics is to distinguish ADHD sensu stricto from other syndromes with partially similar symptoms. If tests of time perception were indeed instrumental in diagnostics [ 21 ], it would be important to know whether alterations in temporal processing are specific to ADHD or rather a trans-nosographic phenomenon. For example, Smith et al [ 44 ] found differing results for children with and without ADHD in a reproduction task when IQ and short-term memory were taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned increase in popularity of computer-assisted assessment tools is partly caused by the fact that it is relatively easy to implement these immediate rewards, to adapt difficulty levels, to implement a story, and to use intrinsic fantasy elements. This leads to a situation in which the child does not have the feeling of being assessed but instead thinks that he or she is playing a game [ 10 ]. This is especially important in tests that are designed for children because it is known that children can behave differently when they know they are being studied (also known as the Hawthorne effect [ 11 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Instruments for detecting timing deficits may enhance accuracy in ADHD diagnosis (cf. Bluschke et al, 2018 ; Gongsook et al, 2014 ). In this regard, the method of time estimation and the measure accuracy score appear to be particularly robust in terms of their high reliability ( Marx et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%